Correlations among tracheal dimensions, tracheal stent dimensions, and major complications after endoluminal stenting of tracheal collapse syndrome in dogs. (9th July 2019) - Violette, Nathaniel P.; Weisse, Chick; Berent, Allyson C.; Lamb, Kenneth E.
Abstract: Background: Endoluminal tracheal stenting can relieve signs associated with tracheal collapse syndrome (TCS) in dogs, but major complications can result. Objective: To identify associations among tracheal dimensions, stent dimensions, and subsequent complications requiring additional stent placement after endoluminal stenting for TCS. Animals: Fifty‐two dogs from the hospital population. Methods: Medical records of dogs that received an endoluminal self‐expanding tracheal stent for TCS by the interventional radiology service between 2009 and 2014 were reviewed for relevant data. Signalment and clinical details, including tracheal collapse type, tracheal measurements, nominal stent dimensions, follow‐up evaluation times, and stent complications, were recorded. Results: Fifty‐two dogs that received an endoluminal stent for TCS met the inclusion criteria. Major complications included stent fracture (13/52; 25%), obstructive tissue ingrowth (10/52; 19%), and progressive tracheal collapse (6/52; 12%). Natural tracheal taper ( P = .04) and more stent diameter oversizing ( P = .04) in the intrathoracic (IT) trachea were associated with caudodorsal stent fracture. Only stents with a 14‐mm nominal diameter fractured. Progressive tracheal collapse was associated with smaller maximum tracheal diameters ( P = .02). The majority of dogs with obstructive tissue ingrowth (7/10; 70%; P = .30) and all dogs with thoracic inlet fractures (3/3; 100%) had tracheal malformations. Conclusions and Clinical Importance: A higher taper in tracheal diameter may lead to increased risk of fracture in the IT location. Dogs with tracheal malformations may have higher risk for thoracic inlet fracture and development of obstructive tissue ingrowth. Clinicians should be aware of the possible risk factors for tracheal stent complications.